University Students’ Preferences and Recognition: British English Vs. American English - Marisa Yoestara; Juwita Wahyuni (International Journal of Education, Language, and Religion, 2022)
British English (BrE) or American English (AmE) are two common English varieties known and used in Indonesia in almost all level of formal education, including in university. This study was intended to find out two folds, which are; (1) the varieties of English the university students prefer to use in spelling and pronunciation; and (2) their ability to recognize the differences between these varieties in vocabulary. The design of this study was a descriptive design which involved 30 students of the English Department at the University of Serambi Mekkah from various semesters but with an average level of English capability. Questionnaire and oral test were used as the instruments to find out the students’ preferences of English varieties in spelling and pronunciation; while, written test is used to find out the students’ ability to recognize the difference of vocabulary within the two varieties. The result of the questionnaire and oral test was analysed by using percentage formula to find out which variation was more dominant in both spelling and pronunciation. Meanwhile, the written test result was checked for its true and false answer in order to decide how far the students could recognize the difference of vocabulary between BrE and AmE. The result showed that more than half of the students preferred to use American English variety in terms of spelling and pronunciation, 55.3% and 60.1% respectively. The results of this study also revealed that 65.2% of the university students had the ability to recognize the differences between BrE and AmE in terms of vocabulary.